DEFECT SELECTIVE ETCHING OF THICK AlN LAYERS GROWN ON 6H-SIC SEEDS – A TRANSMISSION ELECTRON MICROSCOPY STUDY - Nyakiti, Luke Owuor; Chaudhuri, Jharna; Kenik, Ed A.; Lu, Peng; Edgar, James H. (My University, 2009)
In the present study, the type and densities of defects in AlN crystals grown on 6H-SiC seeds by the sublimation-recombination method were assessed. The positions of the defects in AlN were first identified by defect selective etching (DSE) in molten NaOH-KOH at 400 °C for 2 minutes. Etching produced pits of three different sizes: 1.8, 2.4, and 2.9 μm. The etch pits were either aligned together forming a sub-grain boundary or randomly distributed. The smaller etch pits were either isolated or associated with larger etch pits. After preparing cross-sections of the pits by the focused ion beam (FIB) technique, transmission electron microscopy (TEM) was performed to determine the dislocation type (edge, mixed or screw) associated with a specific etch pit size. Preliminary TEM bright field and dark field imaging using different zone axes and diffraction vectors indicates an edge dislocation with a Burgers vector 1/3[1120] is associated with the smallest etch pit size.